Different effects of tirofiban and aspirin plus clopidogrel on myocardial no-reflow in a mini-swine model of acute myocardial infarction and reperfusion. Issue 8 (30th December 2005) - Yang, Y-J; Zhao, J-L; You, S-J; Wu, Y-J; Jing, Z-C; Yang, W-X; Meng, L; Wang, Y-W; Gao, R-L
Abstract : Objective: To compare the effects of an aspirin–clopidogrel combination with those of the specific glycoprotein IIb/IIIa inhibitor tirofiban on myocardial no-reflow, nitric oxide concentration and activity of nitric oxide synthase (NOS) isoforms in a mini-swine model of acute myocardial infarction and reperfusion. Methods: Area of no-reflow was determined by both myocardial contrast echocardiography and pathological means in 40 mini-swine randomly assigned to five study groups: eight controls, eight pretreated with aspirin–clopidogrel combination for three days, eight given an intravenous infusion of tirofiban, eight treated with ischaemic preconditioning and eight sham operated. The acute myocardial infarction and reperfusion model was created with 3 h occlusion of the left anterior descending coronary artery followed by 1 h reperfusion. Results: Compared with the control group, tirofiban significantly decreased the area of no-reflow assessed echocardiographically and pathologically, from 78.5% to 22.8% and 82.3% to 23.2%, respectively (both p < 0.01), and increased blood nitric oxide concentration (p < 0.05), enhanced constitutive NOS activity from 0.51 to 0.81 U/mg protein and mRNA expression from 0.47% to 0.66%, but decreased inducible NOS activity from 0.76 to 0.41 U/mg protein and mRNA expression from 0.54% to 0.39% in reflow myocardium (all p < 0.05–0.01). In contrast, the aspirin–clopidogrel combination did not significantly modify the above parameters (all p > 0.05) except for decreasing inducible NOS activity from 0.76 to 0.39 U/mg protein (p < 0.01) and mRNA expression from 0.54% to 0.40% (p < 0.05). Conclusions: Tirofiban is very effective in attenuating myocardial no-reflow; in contrast, aspirin–clopidogrel combination is totally ineffective. These findings also support the concept that endothelial protection, apart from platelet inhibition, contributes to the beneficial effect of tirofiban on myocardial no-reflow.